2015
DOI: 10.1007/s00204-015-1621-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of high-throughput RT-qPCR to assess modulations of gene expression profiles related to genomic stability and interactions by cadmium

Abstract: Predictive test systems to assess the mode of action of chemical carcinogens are urgently required. Within the present study, we applied the Fluidigm dynamic array on the BioMark™ HD System for quantitative high-throughput RT-qPCR analysis of 95 genes and 96 samples in parallel, selecting genes crucial for maintaining genomic stability, including stress response as well as DNA repair, cell cycle control, apoptosis and mitotic signaling. The specificity of each individually designed sequence-specific primer pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 68 publications
2
61
0
3
Order By: Relevance
“…0.5-1 × 10 6 logarithmically growing BEAS-2B cells were treated with different concentrations of CuO NP, CuO MP or CuCl 2 , with or without 100 µM OH-dyn or 100 nM bafA1 for 8 h or 24 h, respectively, in DMEM containing 10% FCS. Subsequently, gene expression analyses via high-throughput RT-qPCR with Fluidigm dynamic arrays on the BioMarkTM System were performed, as described previously [13]. For normalization, five potential reference genes were available (ACTB, B2M, GAPDH, GUSB and HPRT1).…”
Section: Gene Expression Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…0.5-1 × 10 6 logarithmically growing BEAS-2B cells were treated with different concentrations of CuO NP, CuO MP or CuCl 2 , with or without 100 µM OH-dyn or 100 nM bafA1 for 8 h or 24 h, respectively, in DMEM containing 10% FCS. Subsequently, gene expression analyses via high-throughput RT-qPCR with Fluidigm dynamic arrays on the BioMarkTM System were performed, as described previously [13]. For normalization, five potential reference genes were available (ACTB, B2M, GAPDH, GUSB and HPRT1).…”
Section: Gene Expression Analysesmentioning
confidence: 99%
“…Gene expression analyses via high-throughput qRT-PCR established previously in our group, quantifying the impact of 96 samples in parallel on the expression of 95 genes crucial for maintaining genomic stability. Selected genes were related to metal homeostasis, (oxidative) stress response as well as DNA repair, cell cycle regulation and apoptosis; a detailed description including a complete list of genes and respective proteins as well as their assignments to the respective groups has been published [13]. Applying this approach in a previous study in BEAS-2B cells after treatment with CuO NP, CuO MP as well as CuCl 2 , revealed a strong induction of copper uptake-related metallothionein genes, oxidative stress sensitive and inflammatory genes, anti-oxidative defense-associated genes, as well as the induction of cell cycle inhibitor gene CDKN1A (p21) and the pro-apoptotic PMAIP1 (Noxa) and TNFRSF10B (DR5).…”
Section: Gene Expression Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In unserem Arbeitskreis wurde daher eine quantitative Hochdurchsatz‐Methode zur Analyse von Genexpressions veränderungen (High‐Throughput RT‐qPCR) etabliert, die es ermöglicht, den Einfluss von 96 Proben auf die Expression von 95 Genen parallel zu untersuchen . Es wurden 95 Gene ausgewählt, die eine Beeinflussung der genomischen Stabilität widerspiegeln; sie umfassen neben der Metallhomöostase die DNA‐Schadensantwort, redox‐regulierte Transkriptionsfaktoren, die (oxidative) Stress‐Antwort, Zellzyklusregulation und Proliferation, Apoptose und Fremdstoffmetabolismus.…”
Section: Ausblickunclassified
“…Results of many experimental studies show it. [31][32][33][34][35] Thus, 8 h were enough to alter gene expression, but not enough to induce the massive cell death using Zn-1 in concentrations 1-5 µM. Genes with a definite function and a proved mRNA level reaction to different chemical and physical stress factors were selected.…”
Section: Expression Of Stress Responsive Genes Under Zn-1mentioning
confidence: 99%